1976
DOI: 10.1130/mem145-p375
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary Sediment of the Panama Basin: Sedimentation Rates, Periodicities, and Controls of Carbonate and Opal Accumulation

Abstract: Assuming a constant rate of quartz accumulation for deep-sea sediment core Y69-106P, from the Panama Basin, I have estimated the age of samples from the core and have constructed a curve for sedimentation-rate versus time. Stratigraphic controls for the calculated time scale include three C 14 measurements, the extinction of the radiolarian Stylatractus universus, correlation with oxygen-isotope curves from other dated cores, and an Ar 40 /Ar 39 age determination.The model sedimentation rates, when combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…Even in these cores, however, this factor does not change monotonically with depth. Such a pattern is suggestive of glacial-interglacial changes in surface biologic productivity (Pisias, 1976) which our sampling interval cannot fully resolve.…”
Section: Factormentioning
confidence: 88%
“…Even in these cores, however, this factor does not change monotonically with depth. Such a pattern is suggestive of glacial-interglacial changes in surface biologic productivity (Pisias, 1976) which our sampling interval cannot fully resolve.…”
Section: Factormentioning
confidence: 88%
“…However, other studies have shown a close link between biogenic silica in surface sediment and biosiliceous productivity patterns in overlying waters (e.g., Mortlock and Froelich, 1989;Koning et al, 2002). Further studies have linked downcore traces of biogenic silica to local paleoproductivity records with Milankovitch-like cycles (Mortlock and Froelich, 1989;Pisias, 1976;Pisias and Leinen, 1984).…”
Section: Diatom Valve Preservation and Paleoproductivitymentioning
confidence: 96%
“…Thompson and Saito [ 1974] carded out preservation studies and clearly documented the association of well-preserved microfossils with the high carbonate glacial intervals. Since then, paleocean,graphers have interpreted the Pacific carbonate cycles as dominated by a preservation-dissolution signal, reflecting the changing carbonate chemistry of deep water [Pisias, 1976]. Adelseck and Anderson [ 1978] have argued that cores recovered well above the compensation depth contain a productivity record in the CaCO3 contents.…”
Section: Proxy Indicatorsmentioning
confidence: 99%